Jesus Research: An International Perspective. The First Princeton–Prague Symposium on Jesus Research. Edited by James H. Charlesworth and Petr Pokorný - Twelftree, Graham H. (The journal of theological studies, 2011)
Despite occasional protests, the quest for the historical Jesus continues to be parcelled up in neat phases, as in this work, turning around the succession of landmark contributions. What distinguishes the Third Quest, or what Charlesworth calls ‘Jesus Research’, is that those who seek a Saviour are now in the company of others intent on scientific historiography. The purpose of the reported symposium was to evaluate where we are in the study of the historical Jesus., Stanley Porter argues that, far from shutting down discussion of Jesus, Schweitzer was setting the agenda for subsequent work he hoped would be more historical. Though following in his wake, in what way the development of the criteria for authenticity was a response to Schweitzer’s work is not clarified.